REGIONAL INTEGRATION: MERCOSUR ON THE VERGE OF POLITICAL ORIENTATIONS - Fernandes, Marcelo Pereira; Wegner, Rubia (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The aim of this paper is to analyze the change in the orientation of Brazil’s foreign policy after the beginning of the Temer government, highlighting the main measures related to MERCOSUR. With the appointment of José Serra as Minister of Foreign Affairs, a profound change of position took place in relation to the way in which Brazil has guided its foreign policy since 2003, especially in relation to MERCOSUR. Evidence shows that the focus of South-South integration is likely to give rise to a project of rapprochement with Western powers, notably the United States.